Does Home Remedy Use Contribute to Medication Nonadherence Among Blacks with Hypertension? - Cuffee, Yendelela L. (Ethn Dis, 2020)
BACKGROUND: Home remedies (HRs) are described as foods, herbs, and other household products used to manage chronic conditions. The objective of this study was to examine home remedy (HR) use among Blacks with hypertension and to determine if home remedy use is correlated with blood pressure and medication adherence. METHODS: Data for this cross-sectional study were obtained from the TRUST study conducted between 2006-2008. Medication adherence was measured using the Morisky Medication Adherence Scale, and HR use was self-reported. Multivariable associations were quantified using ordinal logistic regression. RESULTS: The study sample consisted of 788 Blacks with hypertension living in the southern region of the United States. HR use was associated with higher systolic (HR users 152.79, nonusers 149.53; P=.004) and diastolic blood pressure (HR users 84.10, nonusers 82.14 P=.005). Use of two or more HRs was associated with low adherence (OR: .55, CI: .36-.83, P= .004). CONCLUSION: The use of HR and the number of HRs used may be associated with medication nonadherence, and higher systolic and diastolic blood pressure among Blacks with hypertension. Medication nonadherence is of critical importance for individuals with hypertension, and it is essential that health care providers be aware of health behaviors that may serve as barriers to medication adherence, such as use of home remedies.